Deign and build step-down switching regulator - Tan, Yih Horng (2017)
This report explains the basic concepts of regulators and switching mode power supplies. The basic operating principles of both linear and switching regulators are explained. Also, the advantages and disadvantages of each solution are discussed. The step-down switching regulator is used to further explain the design considerations of a switching regulator. A step-down switching regulator was designed and constructed in this hardware project. After the theoretical basis and practical analysis, the input voltage was stepped down using a MC34063A IC chip. A switching regulator was built using IC chip and discrete component to bring down a 12V to 5V power supply.